Effect Of Combination Of Extracts Of Several Rhizomes On Mortality Of Armyworm (Spodoptera sp.) On Sweet Potato Plants (Ipomoea batatas L.) - Simbolon, Syamsuddin; Wahyuni, Siti Hardianti; Friska, Meiliana (FAKULTAS PERTANIAN UNIVERSITAS RATU SAMBAN, 2024)
The use of a mixture of rhizome extracts of red ginger, turmeric, and kencur to control armyworms (Spodoptera litura F.) is an important prospect in increasing the yield of sweet potato crops, because plant-based pesticides can be used in single or mixed forms. The study aimed to determine the influence of various mixed effects of different concentrations of extracts of several rhizomes on the mortality of Grayak caterpillar pest (Spodoptera litura F.) on sweet potato plants (Ipomoea batatas L.). As well as determining the concentration of rhizome extract mixture that is more effective in controlling Grayak caterpillar pests (Spodoptera sp.) on sweet potato plants (Ipomoea batatas L.). This study used a method with a Group Random Design (RAK) consisting of 5 treatments and 5 replicates. The treatment is: 1. Control (sterile water application), 2. A mixture of red ginger, turmeric, and kencur rhizome extracts 40%, 50%, 60%, 70%, 80%, 90% through food (Stomach poison). The experiment was arranged in a complete randomized design of four replicates each using instar 2 larvae of Spodoptera sp. as many as 280 heads. Research Results The observation results showed that there was an influence of each concentration tested on the pest Spodoptera sp. through food (Stomach poison) against the larvae of the second instar where the level of attack caused in the instar is very high, so the concentration used is 40%-90%. All concentrations showed a real effect on the larvae of the two instars, at a concentration of 40% a mortality rate of 11.50%, and the highest concentration was 90% with a mortality rate of 80%..